Genicular axial pattern flap for coverage of a hind limb defect caused by dog bites in a ewe. Issue 3 (7th June 2021) - Pappa, Elena; Zacharopoulou, Theodora; Georgiou, Stefanos; Sideri, Aikaterini; Tsioli, Vassiliki
Abstract: A ewe was referred with severe dog bite wounds after unsuccessful attendance in a first opinion surgery. A large, complex, contaminated wound was evident in the medial surface of the left tibia. Initial management included lavage, surgical debridement, suturing of ruptured muscles and bandaging. Staged debridement was performed repeatedly 7, 14 and 21 days after initial presentation, while open wound management was carried out for 6 weeks. When the left hind limb wound was covered with healthy granulation tissue, the defect was closed with a genicular axial pattern skin flap. Post‐operatively, antibiotics and analgesics were administered; bandages were applied. Flap tip oedema and partial thickness skin loss concerning the epidermis were observed. The ewe recovered after 40 days of post‐operative hospitalisation. On re‐examination, 1 year after initial admission, no complications or lameness was reported. Although therapeutic management required extensive surgical attention and long post‐operative care, the final outcome was favourable.